Association Between Menstrual Cycle Length and Coronavirus Disease 2019 (COVID-19) Vaccination: A U.S. Cohort. Issue 4 (5th April 2022) - Edelman, Alison; Boniface, Emily R.; Benhar, Eleonora; Han, Leo; Matteson, Kristen A.; Favaro, Carlotta; Pearson, Jack T.; Darney, Blair G.
Abstract : Based on prospective population-level data, coronavirus disease 2019 (COVID-19) vaccination is associated with a less than 1-day change in menstrual cycle length but no change in menses length. Abstract : OBJECTIVE: To assess whether coronavirus disease 2019 (COVID-19) vaccination is associated with changes in cycle or menses length in those receiving vaccination as compared with an unvaccinated cohort. METHODS: We analyzed prospectively tracked menstrual cycle data using the application "Natural Cycles." We included U.S. residents aged 18–45 years with normal cycle lengths (24–38 days) for three consecutive cycles before the first vaccine dose followed by vaccine-dose cycles (cycles 4–6) or, if unvaccinated, six cycles over a similar time period. We calculated the mean within-individual change in cycle and menses length (three prevaccine cycles vs first- and second-dose cycles in the vaccinated cohort, and the first three cycles vs cycles four and five in the unvaccinated cohort). We used mixed-effects models to estimate the adjusted difference in change in cycle and menses length between the vaccinated and unvaccinated cohorts. RESULTS: We included 3, 959 individuals (vaccinated 2, 403; unvaccinated 1, 556). Most of the vaccinated cohort received the Pfizer-BioNTech vaccine (55%) (Moderna 35%, Johnson & Johnson/Janssen 7%). Overall, COVID-19 vaccine was associated with a less than 1-day change in cycle length for both vaccine-dose cycles compared with prevaccine cycles (first dose 0.71 day-increase, 98.75% CI 0.47–0.94; second dose 0.91, 98.75% CI 0.63–1.19); unvaccinated individuals saw no significant change compared with three baseline cycles (cycle four 0.07, 98.75% CI −0.22 to 0.35; cycle five 0.12, 98.75% CI −0.15 to 0.39). In adjusted models, the difference in change in cycle length between the vaccinated and unvaccinated cohorts was less than 1 day for both doses (difference in change: first dose 0.64 days, 98.75% CI 0.27–1.01; second dose 0.79 days, 98.75% CI 0.40–1.18). Change in menses length was not associated with vaccination. CONCLUSION: Coronavirus disease 2019 (COVID-19) vaccination is associated with a small change in cycle length but not menses length.